A Nonparametric Operational Risk Modeling Approach Based on Cornish-Fisher Expansion - Xiaoqian Zhu; Jianping Li; Jianming Chen; Yingqi YangHuo; Lijun Gao; Jichuang Feng; Dengsheng Wu; Yongjia Xie (Discrete Dynamics in Nature and Society)
It is generally accepted that the choice of severity distribution in loss distribution approach has a significant effect on the operational risk capital estimation. However, the usually used parametric approaches with predefined distribution assumption might be not able to fit the severity distribution accurately. The objective of this paper is to propose a nonparametric operational risk modeling approach based on Cornish-Fisher expansion. In this approach, the samples of severity are generated by Cornish-Fisher expansion and then used in the Monte Carlo simulation to sketch the annual operational loss distribution. In the experiment, the proposed approach is employed to calculate the operational risk capital charge for the overall Chinese banking. The experiment dataset is the most comprehensive operational risk dataset in China as far as we know. The results show that the proposed approach is able to use the information of high order moments and might be more effective and stable than the usually used parametric approach.